Living Arrangements and Sleep-Related Outcomes Among Older Adults in China: A Panel Analytic Approach. (September 2020) - Lee, Yen-Han; Chang, Yen-Chang; Chiang, Timothy; Liu, Ching-Ti; Shelley, Mack
It has been discussed previously that older adults' living arrangements are associated with mortality. This study investigated the relationships between older adults' living arrangements and sleep-related outcomes in China. The nationally representative sample included 4, 731 participants who participated on two different occasions, with a total of 9, 462 observations (2012 and 2014 waves). Panel logistic regression and panel ordinary least squares regression models were estimated with outcomes of sleep quality and average hours of sleep daily, respectively. Approximately 62% of individuals reported good quality of sleep. We observed that older adults who lived with family members had 17% greater odds of reporting good quality of sleep (adjusted odds ratio = 1.17, 95% confidence interval [1.03, 1.34], p  < .05) and reported longer sleep duration daily (β = .334, standard error = .069, p  < .01), compared with those who lived alone. Social support is needed to strengthen the residential relationship, especially with family members.